(untitled) (Acta Entomologica Serbica, 2016)
During the period 2012-2014, in the experimental field of the Institute of Forage Crops, Pleven, Bulgaria, the side effect of neem and pyrethrum products on banded thrips, Aeolothrips ntermedius Bagnall (Thysanoptera: Thripidae) and the seven-spot ladybird Coccinella septempunctata L. (Coleoptera: Coccinellidae) adults was defined. Treatments were carried out at the beginning of the flowering stage of alfalfa (Medicago sativa L.) in the second intercut. Sweeping with an entomological net was used to collect specimens. It was found that the biological insecticides NeemAzal and Pyrethrum were nontoxic with respect to Coccinella septempunctata adults, and in almost 70% of cases were harmless to Aeolothrips intermedius. Analysis of variance (ANOVA) regarding product toxicity on predatory species demonstrated that the factor B (type of insecticide) had the strongest effect – 89.1 and 82.5% of the total variance for C. septempunctata and A. intermedius, respectively. Tested plant insecticides showed no negative impact on the predatory species and they can be applied in organic seed production of alfalfa.